Social support, financial status, and depression among French healthcare workers one year after the onset of the COVID-19 pandemic - Charline Vincent; Pierre Chauvin; Honor Scarlett; Wissam El-Hage; Roberto Mediavilla; Cécile Vuillermoz (BMC Public Health)
Abstract Background Early studies on factors associated with depressive symptoms among healthcare workers (HCWs) during the COVID-19 pandemic were primarily related to working conditions and exposure to the pandemic. Despite the socio-economic impact of the pandemic, research focusing on factors related to social support and financial situation was scarce. Objectives This study investigated the association between HCWs’ financial and social support, and the presence of depressive symptoms in France one year after the pandemic’s onset. Methods This study used data from a cross-sectional, online, voluntary survey conducted in France between April and October 2021 among a diverse, non-probability sample of HCWs. Data were calibrated according to the French Census of HCWs. Depressive symptoms (moderate to severe) were assessed using the 9-item Patient Health Questionnaire (score > 9). Four log-binomial regression models estimated prevalence ratios (PR) and their 95% confidence intervals (95%CI), taking into account working conditions, sociodemographics, and mental health comorbidities (post-traumatic stress disorder, anxiety, burnout). Results Among the 655 respondents, 21% had moderate to severe depressive symptoms. Adjusted for working conditions and sociodemographics found significant associations between loneliness, lack of social support at work and worsening financial outcomes over the past year, with depression. After introducing mental health comorbidities, not only were they all associated with depression, but worsening financial outcomes and living alone remained associated with depression (PR = 1.23; 95%CI [1.04–1.45] and PR = 1.33; 95%CI [1.13–1.57], respectively). Conclusion This study suggests that one year after the start of the pandemic, factors associated with depressive symptoms were related to social support and financial situation, unlike at the beginning of the pandemic when working conditions and exposure to COVID-19 were more studied and emphasized. These findings highlight the importance of considering the social determinants of health in studies and interventions aimed at improving the mental health of HCWs, and not just their working conditions.